Comparative Analysis of Biochemical Biases by Ligation- and Template-Switch-Based Small RNA Library Preparation Protocols. (4th February 2020) - Meistertzheim, Morgane; Fehlmann, Tobias; Drews, Franziska; Pirritano, Marcello; Gasparoni, Gilles; Keller, Andreas; Simon, Martin
Abstract: BACKGROUND: Small RNAs are key players in the regulation of gene expression and differentiation. However, many different classes of small RNAs (sRNAs) have been described with distinct biogenesis pathways and, as a result, with different biochemical properties. To analyze sRNAs by deep sequencing, complementary DNA synthesis requires manipulation of the RNA molecule itself. Thus, enzymatic activities during library preparation bias the library content owing to biochemical criteria. METHODS: We compared 4 different manipulations of RNA for library preparation: ( a ) a ligation-based procedure allowing only 5′-mono-phosphorylated RNA to enter the library, ( b ) a ligation-based procedure allowing additional 5′-triphosphates and Cap structures, ( c ) a ligation-independent, template-switch-based library preparation, and ( d ) a template-switch-based library preparation allowing 3′-phosphorylated RNAs to enter the library. RESULTS: Our data show large differences between ligation-dependent and ligation-independent libraries in terms of their preference for individual sRNA classes such as microRNAs (miRNAs), Piwi-interacting RNAs (piRNAs), and transfer RNA fragments. Moreover, the miRNA composition is different between both procedures, and more microRNA isoforms (isomiRs) can be identified after pyrophosphatase treatment. piRNAs are enriched in template-switch libraries, and this procedure apparently includes more different RNA species. CONCLUSIONS: Our data indicate that miRNAomics from both methods will hardly be comparable. Ligation-based libraries enrich for canonical miRNAs, which thus may be suitable methods for miRNAomics. Template-switch libraries contain increased numbers and different compositions of fragments and long RNAs. Following different interests for other small RNA species, ligation-independent libraries appear to show a more realistic sRNA landscape with lower bias against biochemical modifications.